KURVA PHILLIPS DI INDONESIA - Maichal, Maichal (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2012)
This paper aims to analyze the existence of the Philips curve in the Indonesian economy, 2000Q1-2010Q3. The results obtained by using OLS method shows that the expectations augmented Philips curve and the New Keynesian Philips curve models cannot give a clear results of Philips curve existence in the Idonesia economy. Shocks variable such as percentage change of exchange rates and crude oil prices provide a very small effect on the inflation rate in Indonesia. Furthermore, the results obtained by using GMM method on the hybrid model of the New Keynesian Philips curve shows that the Philips curve exists in the Indonesian economy.